Edukasi dan sosialisasi gerakan masyarakat cerdas menggunakan obat (Gema Cermat) dengan metode CBIA - Handa Muliasari; Agus Dwi Ananto; Baiq Sofianti Annisa; Lalu Husnul Hidayat; Candra Eka Puspitasari (Universitas Mataram, 2021)
A community service about the education of Gema Cermat has been conducted in Lebah Sempaga village, West Lombok, NTB. The objective of these activities was to increase people’s knowledge and skills regarding the use of medicines in a right and rational way. The community service was held in three main steps of Community Based Interactive Method, namely presentation of the materials of Gema Cermat by pharmacist leader in NTB, assessments of people’s knowledge before and after socialization by using questionnaires, and evaluation of the participant skills in medicine identifications through the presentation of the participant representations. 23 people are participating in these activities, dominated by females with the age of about 29-50 years old. However, only 13 of them were finishing the questionnaires. Overall, the result of assessments, as well as the evaluation, showed that there was a noticeable improvement in the understanding of people about Gema Cermat, the precise and rational ways in using medicines, with the percentage of 16% increase. Hopefully, people in that area could spread the information to others so that the side effects due to the non-appropriate use of medicines will reduce